Applications of ultra-high resolution microcalorimeter gamma-ray spectrometry - Schreiber, Katherine A.; Koehler, Katrina E.; Croce, Mark P.; Stark, Emily N.; McNeel, Daniel G.; Carpenter, Matthew H.; Mercer, David J.; Abel, E. Paige; Archambault, Brian; Arrigo, Leah; Batie, Grey; Becker, Daniel T.; et al. (Frontiers in Nuclear Engineering, 2025)
Ultra-high energy resolution microcalorimeter gamma-ray spectroscopy—with energy resolution 5 to 10 times better than observed in spectra obtained by commercial-off-the-shelf high purity germanium detectors—is an enabling technology for ultra-precise isotope identification and quantification. Microcalorimeter gamma spectroscopy complements measurements requiring high-accuracy mass spectrometry, a costly, destructive analysis technique, and may offer benefits over mass spectrometry in the future. Microcalorimeter detectors are fabricated from superconducting materials and operate at ultra-low temperatures (<0.1 K), properties which permit measurement of spectra with peak full width half maximum (FWHM) of less than 100 eV at 100 keV. The microcalorimeter collaboration between Los Alamos National Laboratory, National Institute of Standards and Technology, and University of Colorado, Boulder has deployed three microcalorimeter gamma-ray spectrometers to nuclear facilities and analytical laboratories so far. These are the Spectrometer Optimized for Facility Integrated Applications (SOFIA), a portable system that can be moved to any facility, and two instruments called the High Efficiency and Resolution Microcalorimeter Spectrometers (HERMES) intended for permanent installation at Idaho National Laboratory and Pacific Northwest National Laboratory. Each spectrometer was customized to satisfy requirements for their specific applications. This work describes samples examined by microcalorimeter gamma-ray spectrometers, including recently irradiated materials, nuclear material from various stages of the fuel cycle, and medical isotope products. It also highlights useful signatures from actinide and fission product gamma-rays that are otherwise infeasible to observe or use for analysis without costly chemical separations and mass spectrometric assay. Microcalorimeter technology provides additional spectral signatures to existing techniques to better constrain the origin and intended use of nuclear and radioactive materials.